Cardiovascular magnetic resonance in endomyocardial fibrosis - Samuals, Petronella; Jermy, Stephen; Moosa, Sulaiman; Ntusi, Ntobeko A.B. (SA Heart Journal, 2020)
Endomyocardial fibrosis (EMF) is an idiopathic disorder of the tropical and subtropical regions of the world, considered endemic in tropical and subtropical Africa and is characterised by development of restrictive cardiomyopathy. Although accurate epidemiological data are lacking, EMF is estimated to be the most common form of restrictive cardiomyopathy globally. We report on a young patient presenting with a stroke diagnosed with EMF and review the role of cardiovascular magnetic resonance in evaluation of EMF.